The Degree to Which students in the first stage of basic education in Damascus Governorate practice positive economic behaviors (Journal of Hama University, 2025)
The research aimed to determine the degree to which students in the first stage of basic education in Damascus Governorate practice positive economic behaviors from the point of view of their teachers. To achieve the research objectives, the researcher used the descriptive analytical method, designed a questionnaire consisting of (16) items and (3) axes in its final form, and applied it to a random sample of (300) male and female teachers.            It was found that the degree to which students in the first stage of basic education in Damascus governorate practiced positive economic behaviors was low in general, and that there were statistically significant differences between the average scores of teachers’ answers to the questionnaire due to the academic qualification variable in favor of teachers who hold master’s degrees, and the absence of differences between them due to the two years variables. Experience and class; Therefore, the research proposed designing the National Center for Design and Development of Educational Curricula at the Ministry of Education in the Syrian Arab Republic, economic and vocational education curricula for the first stage of the basic education, introducing economic and vocational education into the curricula of the first stage of the basic education through the two modules and integrated approaches, and the use of the first stage of basic education teachers in Damascus Governorate includes strategies for developing positive economic behaviors among their students, and cooperation among members of the school community to plan flexible study schedules that allow teachers sufficient time to develop awareness, culture, trends, and economic and vocational skills among students.
Keywords: First stage Students; First stage schools; Positive economic behaviors